European Regulation Affecting Nanomaterials - Review of Limitations and Future Recommendations - Steffen Foss Hansen; Anders Baun (SAGE Publishing, 2012)
After learning about the potential risks associated with various specific nanomaterials, concerns have been raised about adequacy of existing regulation in Europe and what should be done to address any potential regulatory gaps related to nanomaterials. Understanding the limitations of the current regulation in regard to nanomaterials is a starting point in a democratic and transparent process towards adapting existing laws and facilitating an informed discussion about which kind of regulatory options best address the identified limitations. In the following we will introduce key pieces of European legislation affecting nanomaterials, analyze their limitations, and provide a number of recommendations on how these can be overcome. We find that, although nanomaterials are in principle covered by the scope of many of the existing legislative frameworks, it is often unclear, if current regulations are actually applicable when it comes to specific nanomaterials and their diverse applications. Main limitations seem to be: that requirements to do safety evaluations are triggered by production volumes by tonnage not tailored to the nanoscale, the profound lack of (eco)toxicological data, and that thresholds values and occupational exposure limits cannot be established with existing methodologies.